Validation study of randomly selected cases of PTSD diagnoses identified in a Swedish regional database compared with medical records: is the validity sufficient for epidemiological research? - Hollander, Anna-Clara (BMJ Open, 2019)
OBJECTIVES: In Sweden, the patients’ diagnoses are recorded in administrative registers. The research value of these registers is determined by their diagnostic validity, that is, if the diagnosis recorded meets the relevant diagnostic criteria. The aim of the study was to assess the validity of post-traumatic stress disorder (PTSD)-diagnoses as compared with case notes in medical records (MRs) and to test if there was a difference in validity by gender, migration status and those with and without psychotic symptoms. We hypothesised that the validity would be sufficient, using both Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV and DSM-5 but higher according to DSM-IV than DSM-5, and that the validity would be the same for men and women, but different for Swedish-born and migrants, and for those with and without psychotic symptoms. DESIGN AND SETTING: A validation of the register-diagnoses using MRs from treatment centres within the Region of Stockholm to examine whether patients with a register-diagnosis of PTSD fulfilled DSM criteria of PTSD according to the case notes in their MRs. PARTICIPANTS: A random sample of 187 patients aged 18–64, who had been diagnosed with PTSD (F43.1 in the ICD-10) were drawn from the Region of Stockholm’s MR database 2013–2015. PRIMARY OUTCOME MEASURE: Validity of the PTSD diagnoses according to DSM-IV and DSM-5 as proportions of true positives with 95% CI. RESULTS: The hypothesised sufficient validity of the PTSD diagnoses was confirmed. Although the point-estimates for DSM-IV were higher than for DSM-5, the hypothesis that there would be significant differences in validity between DSM-IV and DSM-5 was not confirmed. There were no significant validity differences by gender, migration status and for those with and without psychotic symptoms. CONCLUSIONS: This study has found that validity of the PTSD diagnoses in the register of the Region of Stockholm to be sufficient for epidemiological research.